Stand Equipment and Test Methods of Modern Optical Sights - A. M. Kurganovich; V. A. Stasilovich; I. P. Shishkin; A. P. Shkadarevich (Приборы и методы измерений)
Manufacture of sights with high output characteristics is a prerequisite for achieving the necessary accuracy when shooting. The aim of the work was to analyze the influence of pancratic optical sights’ main parameters on their output performance characteristics.It is shown that in order to achieve the quality level of the world’s best samples, high image quality – no drop in contrast by no more than 30 % of the calculated value, careful manufacturing and control of both mechanical and optical parts, as well as components of the assembly units of products, the technological process of assembly and alignment is necessary.Bench equipment and test methods which made it possible significantly increase the level of serial production are described, also some characteristics of GS3-12×50, GS3-24×56, GS5-25×56 “NTC “LEMT” BelOMO” are presented.